2019
DOI: 10.2147/jpr.s191900
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electroacupuncture decreases Netrin-1-induced myelinated afferent fiber sprouting and neuropathic pain through &mu;-opioid receptors</p>

Abstract: Purpose: We determined whether electroacupuncture (EA) reduces Netrin-1-induced myelinated primary afferent nerve fiber sprouting in the spinal cord and pain hypersensitivity associated with postherpetic neuralgia (PHN) through activation of μ-opioid receptors. Methods: PHN was induced by systemic injection of resiniferatoxin (RTX) in rats. Thirty-six days after RTX injection, a μ-opioid receptor antagonist, beta-funaltrexamine (β-FNA) or a κ-opioid receptor antagonist, nor B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…The time of acupuncture treatment varies from disease to disease. For example, chronic itch model mice are effective for acupuncture treatment for 9 days, while postherpetic neuralgia model mice need acupuncture treatment for 2 weeks to alleviate mechanical allodynia (Li et al, 2019). In a mouse model of TS, we determined that 4 weeks was the optimal treatment duration to alleviate the behavioral stereotypies.…”
Section: Discussionmentioning
confidence: 99%
“…The time of acupuncture treatment varies from disease to disease. For example, chronic itch model mice are effective for acupuncture treatment for 9 days, while postherpetic neuralgia model mice need acupuncture treatment for 2 weeks to alleviate mechanical allodynia (Li et al, 2019). In a mouse model of TS, we determined that 4 weeks was the optimal treatment duration to alleviate the behavioral stereotypies.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous opioids have the same analgesic effect as synthetic opioid drugs but lack addictive properties [7]. Later, researchers found that electroacupuncture stimulation could release endogenous opioids [8] and that needle electrodes could be used to stimulate peripheral nociceptive afferent nerves [9], prompting the nervous system to secrete opioids that act on the μ-receptor for analgesia [10]. Since then, treatments using endogenous opioid theory for sustained analgesia, such as using laser [11], heat [12], and electrical stimulation [13] to induce endogenous opioids, have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…There also have been some researches in the mechanism of acupuncture/EA in treating neuropathic pain. Li et al (2019) found that 6 weeks of EA intervention could activate µ-opioid receptors, inhibit spinal dorsal horn neuron, and thus release pain. Low frequency of EA inhibits neuropathic pain more effectively than high frequency.…”
Section: Discussionmentioning
confidence: 99%